Próba statystycznej interpretacji wyników badań chemizmu siedlisk łąkowych Lubelszczyzny - Tadeusz Przybysz; Józef Borowiec; Agnieszka Kamińska (Agronomy Science, 2003)
The paper deals with the use of some of the statistical methods to find the relations between the content of chemical elements in soils, plants and between soil and plant. The studies have been conducted on the results of the examination made on the basis of the meadow plants in the Lublin Region. It concerned the content of chemical elements in soils and plants. The characteristics of the studied traits, mean value, standard deviation and variation coefficient were calculated. In pairs a comparison was made of the mean element content in soils of 4 types and plants using t-Student test. Correlation analysis and partial correlation analysis was performed to assess the strengths of connection between the contents of chemical elements in the soil and also between their content in plants. The multiple linear regression analysis was useful to establish the functional dependences in the studied elements. A great variety of the features was observed, which was caused by huge and multidirectional differentiation of the studied meadow habitats. By means of partial correlation, the evidence was found that proving a significant correlation for a given pair of elements does not always mean that a significance connection between them actually exists. The applied methods turned out to be useful for a description of the connections in the research of many variables.